AvrA Salmonella Increases TLR4/NF-κB/β-catenin/TGF-β Expressions of Colorectal Cancer Mice Model - Bogi Pratomo Wibowo; Handono Kalim; Husnul Khotimah; Hidayat Sujuti; Ettie Rukmigarsari; Nabila Erina Erwan (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Colorectal cancer (CRC) is reported as the third most frequently diagnosed cancer worldwide. Salmonella infection plays a role in developing this cancer, which is chronically related to the avirulence protein A (AvrA) effector protein produced by the bacteria. This study was conducted to point out the effect of AvrA Salmonella on the occurrence of CRC through the regulation of TLR4/NF-κB/β-catenin/TGF-β expressions in the azoxymethane (AOM)/dextran sodium sulfate (DSS) CRC model.METHODS: A randomized control group post-test-only study was conducted using male Balb/c mice with 30-gram body weight (10-12 weeks), which were divided into three groups, namely the negative control (normal mice without any treatment), positive control (AOM/DSS-treated mice), treatment 1 (T1) (AOM/DSS-treated mice + AvrA Salmonella) groups. Colon tissue was collected and then prepared for immunohistochemistry staining using TLR4, β-catenin, NF-κB, TGF-β, and Ki67 antibodies, whereas apoptotic cells were stained using TUNEL assay.RESULTS: The expressions of TLR4, β-catenin, NF-κB, TGF-β, Ki67, and apoptosis percentage indicated significant differences among the three groups, which statistically showed p<0.05 in all observed parameters. The mean of all parameters was far more significant in the T1 group than in the negative and positive control groups.CONCLUSION: The findings revealed that AvrA Salmonella could increase the expressions of TLR4, β-catenin, NF-κB, TGF-β, and Ki67 and decrease the apoptotic percentage. Thus, AvrA Salmonella influences CRC tumorigenesis through TLR4/NF-κB/β-catenin/TGF-β and is suggested as a potential target in future preventive and curative management for CRC.KEYWORDS: AvrA Salmonella, carcinogenesis, colorectal cancer